Iron toxicity – Its effect on the bone marrow. Issue 6 (November 2018) - Isidori, Alessandro; Borin, Lorenza; Elli, Elena; Latagliata, Roberto; Martino, Bruno; Palumbo, Giuseppe; Pilo, Federica; Loscocco, Federica; Visani, Giuseppe; Cianciulli, Paolo
Abstract: Excess iron can be extremely toxic for the body and may cause organ damage in the absence of iron chelation therapy. Preclinical studies on the role of free iron on bone marrow function have shown that iron toxicity leads to the accumulation of reactive oxygen species, affects the expression of genes coding for proteins that regulate hematopoiesis, and disrupts hematopoiesis. These effects could be partially attenuated by iron-chelation treatment with deferasirox, suggesting iron toxicity may have a negative impact on the hematopoietic microenvironment. Iron toxicity is of concern in transfusion-dependent patients. Importantly, iron chelation with deferasirox can cause the loss of transfusion dependency and may induce hematological responses, although the mechanisms through which deferasirox exerts this action are currently unknown. This review will focus on the possible mechanisms of toxicity of free iron at the bone marrow level and in the bone marrow microenvironment.